The task adaptation method for determining the optical flow problem of interactive objects recognition in real time; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Bagutdinov R. A. Ravil Anatolievich (2017, 2017)
Title screen